A methodology to obtain material design allowables from high-fidelity compression after impact simulations on composite laminates. (December 2020) - Cózar, I.R.; Turon, A.; González, E.V.; Vallmajó, O.; Sasikumar, A.
Abstract: Aeronautical industries address the structural reliability of designs by defining design allowables that account for any uncertainties. The Composite Materials Handbook-17 proposes A/B-basis values as design allowables. In this study, a new methodology to estimate the design allowables of the Compression After Impact (CAI) strength is presented. The CAI strength is predicted with high-fidelity simulations using finite element models featuring in-house constitutive damage models. The uncertainty associated to parameters of the model is defined and propagated to obtain the CAI strength distribution. To efficiently estimate this distribution, a Monte Carlo simulation is carried out employing a response surface previously calibrated with a reduced number of high-fidelity simulations. The A/B-basis values for the CAI strength are estimated from the strength distribution obtained and then compared with experimental results. The methodology proposed allows to reduce the number of experimental tests associated with generating design allowables, thus leading to an optimised cost-effective design.